Pengalaman ODHA Dalam Menjalani Terapi ARV - Antonij Edimarta Sitanggang; Yunida Turisna Oktavia; Eva Kartika Hasibuan (STIKes Murni Teguh, 2022)
The problem of Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) is a health challenge almost all over the world. This problem occurs due to the management of patients who have not been optimal, management is only concentrated on specific therapy and general therapy by relying on antiretroviral therapy (ARV). The use of antiretrovirals (ARVs) in patients who test positive for HIV is an effort to extend the life expectancy of people living with HIV and AIDS (PLWHA) and make them healthier, and more productive by reducing viraemia and increasing the number of CD4 cells. This study aims to explore the experience of PLWHA in undergoing ARV therapy in the work area of ​​the Helvetia Health Center Medan. This research is a qualitative research with a descriptive phenomenological approach. The population of this study was PLWHA who received ARV in the working area of ​​Helvetia Health Center Medan. The number of participants is 6 people and the data saturation has been achieved and taken using purposive sampling technique. Data collection by in-depth interviews. Data were analyzed using N.Vivo software version 12.0 trial. The results of the research obtained from the results of the interviews that there are 3 themes, 4 sub-themes and 6 categories. Where the 3 themes are experiencing obstacles in obtaining ARVs, finding ways to overcome them in obtaining ARVs and getting motivation to consume ARVs. In conclusion, the participants in this study carried out various stages in obtaining ARVs, even though there were obstacles and support in obtaining ARVs, they continued to consume ARVs regularly, considering that ARVs can extend the life expectancy of PLWHA. Abstrak Permasalahan Human Immunodeficiency Virus (HIV) dan Acquired Immune Deﬁciency Syndrome (AIDS) menjadi tantangan kesehatan hampir di seluruh dunia. Permasalahan itu terjadi akibat penatalaksanaan penderita yang belum optimal, penatalaksanaan hanya dikonsentrasikan pada terapi khusus dan terapi umum dengan mengandalkan terapi antiretroviral (ARV). Penggunaan antiretroviral (ARV) pada pasien dengan hasil tes HIV positif merupakan upaya untuk memperpanjang umur harapan hidup Orang Dengan HIV AIDS (ODHA) dan membuat mereka lebih sehat, dan lebih produktif dengan mengurangi viraemia dan meningkatkan jumlah sel-sel CD4. Penelitian ini bertujuan untuk menggali pengalaman ODHA dalam menjalani terapi ARV di wilayah kerja puskesmas Helvetia Medan. Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologi deskriptif. Populasi penelitian ini adalah ODHA yang mendapatkan ARV di wilayah kerja puskesmas Helvetia Medan. Jumlah partisipan sebanyak 6 orang dan sudah tercapainya saturasi data yang diambil dengan teknik purposive sampling. Pengumpulan data dengan wawancara mendalam. Data dianalisis dengan menggunakan software N.Vivo versi 12.0 trial. Hasil penelitian yang didapatkan dari hasil wawancara yaitu terdapat 3 tema, 4 subtema dan 6 kategori. Dimana 3 tema tersebut yaitu mengalami hambatan dalam memperoleh ARV, mendapatkan cara mengatasi dalam memperoleh ARV dan mendapatkan motivasi mengkonsumsi ARV. Kesimpulannya partisipan dalam penelitian ini melakukan berbagai tahapan dalam memperoleh ARV meskipun ada hambatan dan dukungan dalam memperoleh ARV mereka tetap rutin mengkonsumsi ARV, mengingat ARV dapat memperpanjang angka harapan hidup ODHA.